A phytochemical study of the Cuphea glutinosa from Southern Brazil: Na+, K+-ATPase activity inhibition and antioxidant properties. Issue 23 (2nd December 2019) - Zago, Adriana M.; Carvalho, Fabiano B.; Gutierres, Jessié Martins; Bohnert, Crystiani; Fernandes, Marilda da Cruz; Morandini, Liziane M.; Coelho, Helena S.; Fogaça, Aline O.; Andrade, Cinthia M.; Mostardeiro, Marco A.; Dalcol, Ionara I.; Morel, Ademir F.
Abstract: This study investigated the antioxidant activity of Cuphea glutinosa (CG) and its effect on Na +, K + -ATPase from cardiac muscle . The ethanolic extract showed higher antioxidant capacity compared to aqueous and ethyl acetate fraction. Ethyl acetate fraction showed β-sitosterol-3-O-β-glucoside, kaempferol, quercetin, isoquercetin, gallic acid methyl ester, and gallic acid. The ethanolic extract also reduced the Na +, K + -ATPase activity. CG presented a promising antioxidant activity and inhibitory effect on the Na +, K + -ATPase activity, supporting biochemical evidences the popular use of this plant in the treatment of heart failure. Abstract :